On hidden symmetries and solutions of the nonlinear d’Alembert equation - Barannyk, Anatoliy; Barannyk, Tatiana; Yuryk, Ivan (My University, 2013)
Non-Lie symmetries of nonlinear d’Alembert equation in the pseudo-Euclidean space R2;2 are studied and new classes of exact solutions are constructed. Вивчаються неліївські симетрії нелінійного рівняння Даламбера в псевдо-евклідовім просторі R2; 2
Keywords: exact solution; nonlinear d’Alembert equation; non-Lie symmetry; точні розвязки; неліївська симетрія; нелінійне ріняння Даламбера; кафедра вищої математики імені проф. Можара В. І.